PENGARUH CSR DAN TINGKAT UTANG TERHADAP PENGHINDARAN PAJAK (Kajian pada Perusahaan Tercatat di BEI Pada 2019 – 2021) - Muhammad Hafizh Zidane; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to see and evaluate CSR and debt levels on tax avoidance in LQ45 corporations listed on the Indonesia Stock Exchange in the period 2029 – 2021. CSR and debt levels are two of the practices that have the potential to influence tax evasion.This study uses multiple linear regression method. CSR is assessed using CSR values based on Bloomberg's laboratory, liabilities are assessed using the Debt to Equity Ratio (DER), and tax evasion is measured by the Effective Tax Rate (ETR).The results obtained within this research are that CSR has no impact on tax evasion, furthermore, the extent of liabilities impacts taxation evasion. CSR affects tax avoidance positively, while debt levels affect tax avoidance negatively.